A rectification-free piezo-supercapacitor with a polyvinylidene fluoride separator and functionalized carbon cloth electrodes1. Issue 29 (7th August 2015) - Song, Ruobing; Jin, Huanyu; Li, Xing; Fei, Linfeng; Zhao, Yuda; Huang, Haitao; Lai-Wa Chan, Helen; Wang, Yu; Chai, Yang
<x xml:space="preserve">Abstract</x> The integration of energy harvesting and energy storage in this device not only enables the conversion of ambient energy into electricity, but also provides a sustainable power source for various electronic devices and systems.